Simulation for Optimizing the Design of Cryogenic Stopping Cell for the IGISOL Facility at ELI-NP - Anh, Le Tuan; Cuong, Phan Viet; Constantin, Paul; Balabanski, Dimiter; Mei, Bo; Ha, Nguyen Hong; Thao, Ho Thi; Thanh, Kim Tien; Vinh, Nguyen The; Khue, Pham Duc (Communications in Physics, 2019)
The production of the exotic neutron-rich ion beams from photofission of the actinide targets in an IGISOL facility will be studied via an experimental program that will take place at the Extreme Light Infrastructure - Nuclear Physics (ELI-NP) facility. Geant4 simulation toolkit was used for optimizing the target configuration in order to maximize the rate of released photofission fragments from targets placed in a cell filled with He gas.